Effect of the Application of the Technique of Bulk-fill Composite Restorations on Microleakage of Primary Teeth (An In-Vitro Comparative Study) (Journal of Hama University, 2021)
Objectives: This study aimed to assess and compare the microleakage of two bulk fill and one conventional composite in class II restorations of primary posterior teeth.Materials and methods: This in vitro study was conducted on 60 primary second maxillary and mandibular molars, which were randomly divided into three groups. Standard class II cavities were prepared in teeth and restored with Filtek Bulk Fill composite (3M) in group 1, SonicFill 2 bulk fill composite (Kerr) in group 2 and Filtek Z250 conventional composite (3M) in group 3. Single Bond Universal bonding agent was used in all cavities. The teeth were them thermocycled 5°-55° (500 cycles) and immersed in mythelene blue 2%. The teeth were then mesiodistally sectioned and evaluated under a stereomicroscope at 10× magnification. Dye penetration was recorded and data were analyzed using the appropriate statistical methods.Results: Analysis showed no statistically differences between the studied groups except for microleakage between group 1 and 2, in which SonicFill 2 exhibited better results compared to Filtek Bulk Fill.Conclusions: Results of this study showed that there is no difference between SonicFill 2 (bulk-fill technique) and Filtek Z250 (layering technique) in restoring class II restorations in primary teeth in terms of microleakage, while using SonicFill 2 is advantageous in comparison with Filtek Bulk Fill (bulk-fill technique).